O aprendizado de inglês em contextos de demandas socioculturais dos Karajá de Buridina - Silva, Valdilene Elisa da (2017)
The aim of this research is to attend the real demand of this indigenous Karajá to communicate with the people to visit the community and talk English, these people want to understand the main that the handcraft has in the indigenous culture. Hence, it’s necessary to ability the indigenous to use the language to tell about your linguistic and cultural reality. Moreover, to promote the documentation of the handcraft made for them, to write small texts about the community and the Aruanã city. Not only in this research but also in the dissertation the theoretical basis are the concepts of Walsh (2001), Pimentel da Silva (1994), (1995), (2001), (2009), (2015) Nunes (2009), Tubino (2005) and others. These authors contribute with the methodologies used in class, using indigenous experience and the conceptions these authors have about minority community in intercultural relation. This way, we develop in the course of English, methodologies of the context, cooperation, learning in communion, and complementarities. The priority is the dialogue between participants an researcher in class, in the community and/or online. It is noticeable with the development of the research, that the knowledge to communicate in English approximated indigenous and tourists in the commercial and cultural relations. Therefore, the indigenous demonstrate satisfaction, gratification when they talk about Karajá culture through their English vocabulary.